Tulip transcription factor TgWRKY75 activates salicylic acid and abscisic acid biosynthesis to synergistically promote petal senescence - Meng, Lin (Journal of experimental botany, 2024)
© The Author(s) 2024. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.